Reproductive health professional's reported knowledge on diagnosis and management of rheumatic heart disease in pregnant women in Maputo, Mozambique. (15th October 2020) - Jamal, K.; Raivoso, M.; Daniel, A.; Mocumbi, A.
Abstract: Background: Rheumatic heart disease (RHD) poses a threat to African women in their reproductive years, being an important cause of maternal mortality and poor foetal outcomes. Timely diagnosis and adequate management reduce significantly obstetric complications. Our study aimed to describe the knowledge of diagnosis and management of RHD in pregnant women among reproductive health professionals (RHP) working in a highly endemic area. Methods: The study that took place in May/2017 in two conveniently selected health facilities. Doctors (residents and specialists) and mid-level (maternal and child health nurses/technicians, MLRHP) were invited to respond to an anonymous, self-administered and standardized survey (electronic and paper-based questionnaires), which contained closed and open-ended questions on pregnancy-related RHD diagnosis, treatment and complications. The responses were coded and analysed using SPSS version 20. Results: Seventy-three RHP participated (27 doctors, 46 MLRHP). While RHP understand the fetal 49 (67%) and maternal 57 (53%) outcomes in presence of RHD, they are unprepared to diagnose, manage and refer them adequately. Conclusion: RHP constitute a group that can be targeted for decentralization of diagnosis and management of RHD, a strategy that may be crucial to reduce maternal mortality by indirect causes in low-middle income countries. Highlights: The 25% contribution of cardiovascular disease to deaths related to pregnancy must not be overseen in Africa. Reproductive Health Workers in Afruca should be able to detect Rheumatic Heart Disease (RHD) in pregant women Ideally, women with RHD should be given pre-conception counseling and be followed since early stages of pregnancy Reproductive health professionals in Mozambique reported low knowledge of diagnosis and manage RHD in pregnancy Targeting RHW for training in RHD diagnosis and management is key to reduce indirect maternal mortality in Africa.